Implementasi Konsep Kampus Berkelanjutan di Universitas Indraprasta PGRI Berdasarkan Kategori Tata Letak dan Infrastruktur - Nindi Risna Dewi; Andrianto Kusumoarto; Rahmat Rejoni (Lakar: Jurnal Arsitektur, 2023)
A sustainable campus is a concept that implements sustainable development in aspects of campus environmental management. A sustainable campus emerges from academic awareness of the importance of the campus contributing to maintaining the integrity of the current environment for future generations, starting on the campus environment. This research was conducted on the basis of measuring the application of the sustainable campus concept in the site and infrastructure category within the UNINDRA B Campus environment. Data collection was carried out through observation, measurement surveying, interviews and documentation studies to obtain the necessary data. Then the data obtained was processed using scoring and mixed method research methods, then analyzed descriptively. In this study, respondents were parties who understood development developments reviewed in the category of UNINDRA B site and infrastructure facilities. After measuring each indicator in the site and infrastructure category, the following scoring is obtained: 1) Ratio of Open Space to Total Area (180 points), 2) Ratio of Open Space to Higher Education Population (30 points), 3) Area area planted with forest plants (60 points), 4) area planted with plants (100 points), and 5) area that cannot be impregnated with water (0 points). The total score for the site and infrastructure category is 370 of the maximum points for all indicators, namely 1500 points. Based on the measurement results of implementing a sustainable campus within UNINDRA B, it still needs to be improved. Improvements in the achievement of site and infrastructure indicators that have not been maximized need to be pursued such as expanding open space along with the addition of facilities inside, expanding space planted with forest vegetation and also reducing pavement areas that cannot be impregnated with water.